Analysis of Semester 4 Student Procedural Error Knowledge In Determining Minimum Path Using Dijkstra Algorithm - ., Zaini (Udayana Journal of Social Sciences and Humanities; Vol 3 No 2 (2019): UJoSSH, September 2019, 2019)
The focus of this research is the determination of the shortest route by students by applying the Dijkstra algorithm which has many benefits in the informatics area. The sample of this research were 4 students who had heterogeneous abilities. The results showed that 75% of the failed samples due to calculation errors. Students with high abilities are easier to understand and skilled at using procedural knowledge compared to students with medium and low abilities.